Grape Root Borer Pest Management in Florida Vineyards - Scott W. Weihman; Oscar E. Liburd (EDIS)
The most important insect pest of grapes in Florida is the grape root borer, Vitacea polistiformis (Harris), a sesiid moth. The grape root borer (GRB) is native to the eastern United States, and ranges south of a line from Vermont across to Minnesota and east of the Mississippi River states, and occurs throughout peninsular Florida. Grape root borer have been damaging vineyards in the southeastern U.S. for over 150 years. It has been declared the most destructive insect pest of grapes in many states including Georgia, North Carolina, and Florida.  This document is Fact Sheet ENY-831, a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2005.